LC-QTOF-MS/MS metabolic profiling and hepatoprotective effects of Litsea monopetala bark methanol extract against liver injury in rats and HepG2 cells: Hepatoprotective potency of Litsea monopetala - Sahoo, Subhasish; Khan, Haseeb A.; Kar, Durga Madhab; Pattanaik, Sovan; Rath, Diptirani (Cellular and Molecular Biology, 2024)
Fresh stem bark decoction of Litsea monopetala has been practiced for the treatment of jaundice and other liver disorders by the tribal communities of Thakht-e-Sulaiman hills from West Pakistan. As per the folkloric claim, this study aims to identify the phytoconstituents and evaluate the hepatoprotective action of stem bark methanol extract of L. monopetala (LMME). The in-vitro hepatoprotective effect of L. monopetala was performed by H2O2-induced toxicity in the HepG2 cell line and in-vivo by cclt;sub>4-induced hepatotoxicity in Wistar albino rats taking Silymarin as standard drug. Phytoconstituents were identified using LC-QTOF-MS analysis followed by in-silico docking and validation. Molecular docking interactions between identified compounds of L. monopetala and two target proteins, namely 1VJY and 5HYK were presented. In this study, treatment with LMME at 100 µg/mL showed 67.73 % cell viability as compared to H2O2 (100 µM) treated alone i.e., 18.55 % in the HepG2 cell line. In-vivo treatment of LMME reversed the altered serum biochemical parameters and reduced the inflammatory response similar to that of the Silymarin-treated group supported by histopathological investigation. This research reveals that L. monopetala is a rich source of flavonoids and phenols which supports its hepatoprotective effects and is proposed for its usage as a promising hepatoprotective agent after controlled trials